The Role of Inflammatory Biomarkers (IL-6, TNF-α, CRP), Platelet Activation (CD62P, PAC-1, GPIIb/IIIa), Genetic Expression (SERPINE1, F3) and Predictive Modeling Between Depression and Thrombosis Risk: Inflammatory Biomarkers (IL-6, TNF-α, CRP), Platelet Activation (CD62P, PAC-1, GPIIb/IIIa), Genetic Expression (SERPINE1, F3) - Zhang, Jinxia; Liu , Weijian (Journal of Medical Biochemistry, 2026)
Background: Depression is a prevalent psychiatric disorder affecting over 280 million individuals worldwide and is increasingly linked to a higher risk of thrombotic events, such as deep vein thrombosis (DVT) and pulmonary embolism (PE). The underlying biological pathways connecting depression to thrombosis, including systemic inflammation, platelet hyperactivation, and coagulation abnormalities, remain insufficiently understood. This study aims to elucidate these mechanisms by analyzing inflammatory and coagulation biomarkers, assessing platelet function, and identifying independent risk factors for thrombosis. Methods: A case-control study was conducted involving 500 participants: 250 diagnosed with major depressive disorder (MDD) and 250 healthy controls. Key inflammatory markers (IL-6, TNF-α, CRP) and coagulation factors (D-dimer, fibrinogen) were quantified using enzyme-linked immunosorbent assay (ELISA) and quantitative polymerase chain reaction (qPCR). Platelet activation was evaluated via flow cytometry by measuring CD62P (P-selectin) expression, PAC-1 binding, and GPIIb/IIIa activation. A 12-month longitudinal follow-up was performed, and multivariate regression models were employed to identify independent predictors of thrombosis risk. Results: Participants with depression exhibited significantly elevated levels of inflammatory and prothrombotic biomarkers compared to controls (p < 0.001). Markers of platelet activation were notably upregulated, indicating a hypercoagulable state. Multivariate regression analysis identified depression severity (OR = 2.10, 95% CI: 1.80–2.45), IL-6 levels (OR = 1.92, 95% CI: 1.65–2.30), and platelet activation (OR = 2.50, 95% CI: 2.05–3.00) as strong independent predictors of thrombosis risk (p < 0.001). Conclusion: Depression is an independent risk factor for thrombosis, mediated through pathways involving systemic inflammation and platelet hyperactivity. These findings underscore the importance of integrating psychiatric evaluation into thrombosis risk assessment protocols and suggest potential benefits of targeted anti-inflammatory or antiplatelet strategies in high-risk psychiatric populations.